Analysis of Teachers' Workload at Sdn Sumur Peuteuy, Baros Subdistrict, Serang Regency - Ilham Jagat Prediksa; Muhammad Suparmoko; Ende Ende (Universitas Dharmawangsa Medan, 2026)
This study aims to analyze the dimensions of teacher workload, identify the factors that influence it, describe the impacts it generates, and formulate workload management strategies for teachers at SDN Sumur Peuteuy, Baros District, Serang Regency. This study employs a qualitative approach using a case study method. Data were collected through structured interviews, non-participant observation, and documentation study involving four teacher informants selected using purposive sampling, then analyzed using the Miles, Huberman, and Saldana model. The findings indicate that teacher workload is hidden in nature, with the mental dimension being the most dominant. The primary contributing factor is the limited number of teaching staff, followed by educational policy demands and curriculum requirements, as well as workplace dynamics. The impacts include hidden productivity decline, cumulative physical fatigue, and accumulated psychological exhaustion. The workload management strategies currently applied are informal and organic in nature. Teacher workload falls within the moderate to heavy category, necessitating more structured improvement strategies per causative factor across three time horizons, ranging from task distribution remapping to the addition of teaching staff as the most fundamental solution.